The effect of procaine on the mechanical and enzyme activity of ileum smooth muscle of the rat - Saad, Khalid H. M (Al-Mukhtar Journal of Sciences, 2009)
These experiments were a trial to find out the effect of procaine on the spontaneous rhythmic contraction and on the enzyme activity of the mitochondria and membrane vesicles of the smooth muscle of the rat ileum. Procaine has been used at different levels of concentrations. It was found that the very low and low concentrations(O.OOlto O.SmM) increase the tone and enhance the rhythmic spontaneous contractions, mean while concentrations of the drug (3-SmM) induced contracture and reach its maximum level at 8mM of Procaine. Use of very high concentrations (10 -lSmM) caused reverse effect; it induced immediate relaxation to the normal spontaneous contractions. These results might indicate that the procaine exerted its action on this muscle by its interaction with Ca2+ influx through the cell membrane. These hypotheses is confirm.ed by the effect of the drug on the enzyme activity where the drug in low and moderate concentrations enhance the enzyme activity whereas high concentration inhibited the activity